Cartesian dualism and disabled phenomenology. Issue 2 (2nd April 2016) - Abrams, Thomas
ABSTRACT: In this paper, I critically examine phenomenological disability studies' critique of so-called 'Cartesian Dualism'. I argue that it is not a metaphysical divide between mental and extended substance that disability studies must overcome, but rather a more fundamental understanding of world understood only in terms of substance, what Martin Heidegger calls the 'ontology of objective presence'. This view of 'the world' passes over being-in-the-world and the problem of meaning. After outlining phenomenological disability studies' objection to Descartes' legacy, I critically contrast the mind–body problem with the substance problem, suggesting the latter is crucial, and the former derivative. I conclude by discussing the contours of a disabled phenomenology: one that takes physical and mental difference as the basis for a theoretical project, rather than another site for phenomenological investigation.